The impact of ISIS control on the livestock sector in Iraq (a study in geopolitics) (Raparin Journal of Humanities (RJH), 2020)
Livestock resources experienced a dramatic decline in each of Nineveh, Anbar, Salah Al-Din, and parts of Kirkuk and Diyala provinces due to the Islamic states invasion into those areas in June 2014.According to estimates by some international organizations in Iraq, Livestock numbers decreased significantly by 65% ​​from what it was in 2010. Major reasons for Livestock decline in Iraq were conflict, military operations, aerial bombardment, banditry, and lack of health care resulted in the deaths of large numbers of Livestock, in addition to forced internal migration, that resulted in the migration of about four million Iraqis where they had to leave their homes towards western and northern Iraq.  It can be concluded that due to the dramatic decline in Livestock, Iraq lost more than 1.674 billion dollars.